Concrete-filled double skin steel tubular column with hybrid fibre reinforced polymer post fire repair - Kok, Keong Choong; Jaganathan, Jayaprakash; Mohd Zuki, Sharifah Salwa; Shahidan, Shahiron; Ramzi Hannan, Nurul Izzati Raihan (Springer, 2021)
The concrete-filled double skin steel tubular (CFDST) column is becoming more popular nowadays due to its superior performance compared to conventional composite column and concrete-filled steel tubular (CFST) column. However, the use of this type of column is still limited to outdoor construction such as bridge piers and transmission towers where fire is not the main concern. Moreover, existing research studies on the CFDST column only focused on fire performance, and limited research studies can be found on the residual strength of theCFDSTcolumn. Residual strength can be used to determine the most suitable repair method needed in order to retrofit the column. Therefore, this study aims to study the effect of different parameters on the residual strength of the CFDST column. Among discussed parameters are the thickness of the outer steel tube (t0) and fire exposure time. In addition, this study also aims to determine the effectiveness of the repair method using Single and Hybrid fiber-reinforced polymer (FRP) of fire-damaged CFDST columns. CFDST columns were heated in accordance with ASTM E119-11: Standard Test Methods for Fire Tests of Building Construction and Materials until the temperature reached 600 °C. Afterwards, the temperature was kept constant for two different durations, i.e., 60 and 90 mins. The specimen was then left to cool down to room temperature inside the furnace before itwas taken out and repaired by Single and Hybrid FRP. The specimens were categorized into the following three groups: (1) unheated or control specimens, (2) heated and unrepaired specimens and (3) heated and repaired specimens. All specimens were subjected to axial compression loading until failure. The first and second category specimens failed by local outward buckling of outer steel tube, crushing of concrete and local buckling of inner steel tube, whereas specimens in the third category failed by rupture of FRP followed by similar local buckling and concrete crushing as those observed in first and second category specimens. Ultimate strength, secant stiffness and Ductility Index (DI) decreased as the temperature of the specimen increased. The loss in secant stiffness of thinner CFDST specimens exposed to 60 mins of fire exposure time is similar to thicker CFDST specimens exposed to 90 mins of fire exposure time regardless of their diameter. In addition, CFDST specimens exposed to 90 mins of fire exposure time were more ductile than control specimen. RSI and secant stiffness increased with the increase in fire exposure time. Interestingly, the highest RSI achieved is only 22% whichmeans the specimens were still able to carry more than 70% of their initial load after being exposed to 90 mins of fire exposure timewith only 3mmthickness of outer steel tube. Repairing the fire-damaged CFDST columns with Single and Hybrid FRP is proven to improve the ultimate compressive strength significantly. The increment in ultimate compressive strength is more pronounced in the specimen with Hybrid FRP and thinner outer steel tube. The secant stiffness and Ductility Index (DI) of repaired specimens were, however, not able to be restored to those of the control specimen.